MicroRNA-126-3p Inhibits Angiogenic Function of Human Lung Microvascular Endothelial Cells via LAT1 (L-Type Amino Acid Transporter 1)-Mediated mTOR (Mammalian Target of Rapamycin) Signaling. Issue 5 (May 2020) - Cao, Danting; Mikosz, Andrew M.; Ringsby, Alexandra J.; Anderson, Kelsey C.; Beatman, Erica L.; Koike, Kengo; Petrache, Irina
Abstract : Objective: MicroRNA-126-3p (miR-126) is required for angiogenesis during organismal development or the repair of injured arterial vasculature. The role of miR-126 in lung microvascular endothelial cells, which are essential for gas exchange and for lung injury repair and regeneration, remains poorly understood. Considering the significant heterogeneity of endothelial cells from different vascular beds, we aimed to determine the role of miR-126 in regulating lung microvascular endothelial cell function and to elucidate its downstream signaling pathways. Approach and Results: Overexpression and knockdown of miR-126 in primary human lung microvascular endothelial cells (HLMVEC) were achieved via transfections of miR-126 mimics and antisense inhibitors. Increasing miR-126 levels in HLMVEC reduced cell proliferation, weakened tube formation, and increased cell apoptosis, whereas decreased miR-126 levels stimulated cell proliferation and tube formation. Whole-genome RNA sequencing revealed that miR-126 was associated with an antiangiogenic and proapoptotic transcriptomic profile. Using validation assays and knockdown approaches, we identified that the effect of miR-126 on HLMVEC angiogenesis was mediated by the LAT1 (L-type amino acid transporter 1), via regulation of mTOR (mammalian target of rapamycin) signaling. Furthermore, downregulation of miR-126 in HLMVEC inhibited cell apoptosis and improved endothelial tube formation during exposure to environmental insults such as cigarette smoke. Conclusions: miR-126 inhibits HLMVEC angiogenic function by targeting the LAT1-mTOR signaling axis, suggesting that miR-126 inhibition may be useful for conditions associated with microvascular loss, whereas miR-126 augmentation may help control unwanted microvascular angiogenesis. Abstract : Supplemental Digital Content is available in the text.